Integrasi Keterampilan Proses Sains dalam Pembelajaran Melalui Model Pembelajaran Inquiry untuk Meningkatkan Literasi Sains Peserta Didik SDN Magersari 2 Sidoarjo - Novaria Lailatul Jannah (DIDAKTIKA, 2025)
Science literacy is one of the essential competencies that students must have in facing the challenges of the 21st century. However, the results of international assessments show that the science literacy of students in Indonesia is still low. One of the factors contributing to the low science literacy is the lack of integration of science process skills in learning. This study aims to integrate science process skills in science learning through a guided inquiry learning model to improve students' science literacy. The research method used was an experiment with a one group pretest-posttest design. The subjects of the study were fifth grade students of Magersari 2 Elementary School, Sidoarjo. Data were collected through observation, science literacy tests, and interviews with teachers and students. The results showed that the application of the guided inquiry learning model significantly improved students' science process skills and science literacy. Students became more active in making observations, asking questions, interpreting data, and drawing conclusions based on the results of the investigation. Thus, the integration of science process skills in the guided inquiry learning model can be an alternative effective learning strategy to improve elementary school students' science literacy.